Efficacy of immunosoppressive therapy and steroid sparing effect in interstitial lung disease associated to antisynthetase syndrome - G. De Marchi; L. Quartuccio; N. Franzolini; S. De Vita (PAGEPress Publications, 2011)
Objective: To evaluate the role of bronchoalveolar lavage (BAL) in patients with interstitial lung disease associated to antisynthetase syndrome. Methods: We describe 5 patients, anti-Jo1 positive, with interstitial lung disease (lung fibrosis and/or diffusion capacity of CO <80%). Patients were monitored with lung function tests every 6 months, with high-resolution computed tomography (HRCT) every 12 months, and with bronchoalveolar lavage (BAL) at baseline and in the subsequent follow-up. Patients were treated as follows: a) azathioprine with colchicine, or cyclosporine alone b) cyclophosphamide when high neutrophil or eosinophil count on BAL was observed. Only low-dose steroids were used for mild muscular or articular involvement. Results: Pulmonary involvement remained stable in all patients at months +24. Lung function remained unchanged compared to the baseline evaluation; HRCT was stable in patients with fibrosis and no progression into fibrosis was observed in patients with ground glass areas at baseline. Bacterial pneumonia occurred in one patient treated with cyclophosphamide and resolved after antibiotic therapy. Conclusions: Clinical manifestations, instrumental tests and BAL may be of value to choice the best immunosuppressive therapy in the single case. An early less aggressive approach (azathioprine with colchicine, or cyclosporine alone) may be useful. BAL could be performed when a progression of the lung involvement is demonstrated in the subsequent follow-up. Cyclophosphamide may be a valid alternative treatment in the presence of a neutrophilic or eosinophilic alveolitis. Efficacy and safety of the aforementioned immunosuppressive approach were observed in our series, avoiding prolonged high-dose steroid administration.